Exploring lecturers’ experiences in teaching writing skills through online learning - Risnawati Taslim; Naniek Jusnita; Abdulhalim Daud; Agus Supriadi; Hamida Jasin (Jurnal Langua, 2025)
The purpose of this research was to explore the experiences of three lecturers in teaching writing online, the types of online learning platforms used, the techniques employed in teaching writing online, and the challenges faced by the lecturers. This research applied a descriptive qualitative method, and three lecturers participated as respondents in this research. Data were collected through interviews and a checklist questionnaire, and the data were analyzed using content analysis. The results showed that in teaching writing online, the lecturers used some online learning platforms they were familiar with, such as WhatsApp Messenger, Virtual Class, Zoom meeting, and Google Meet. Further, in terms of techniques in teaching writing, it is found that the lecturers use the Picture technique, Reading technique, Teaching organization technique, Controlled writing technique, Mind mapping, and List techniques. It was also found in this research that there were several challenges faced by the lecturers during teaching writing online, including (1) Lecturers faced challenges in controlling students while writing their drafts; (2) Lecturer sometimes face challenges of time management; (3) It takes time to access the online learning platform, and some online platforms require a payment; and lastly, (4) the lecturers have limited access to the internet.